AN ANALYSIS OF FIGURATIVE LANGUAGE IN COLDPLAY’S SONG LYRICS - Komaria, Esti; Rohani, Tri; Fitrilia, Ise (Pattimura Excellence Journal of Language and Culture, 2025)
Figurative language is a way of beautifying certain expressions by using different words which have different meanings from their literal meanings. This study examines the use of metaphorical expressions in Coldplay's song lyrics. The data source were taken from ten songs of Coldplay’s various albums. The goal of this study is to identify the most common form of metaphorical language used in Coldplay’s song lyrics. The qualitative descriptive method was employed in this study. The results of this research show that the total number of figurative language expressions used in Coldplay’s song lyrics were 52 expressions. There were 12 metaphor, 11 personification, 8 hyperbole, 8 symbol, 7 synecdoche and 6 simile. The most dominant type of figurative language expression found in this study was metaphor. Therefore, it is important that teachers can bring this types of figurative language in their classrooms in order for students to get used to using and understand them.